The epidemiology and diagnostic approach to acute pulmonary embolism in the University Hospital - Sharma, Mirella (Array, 2009)
Abstract: The aim of this retrospective study was to evaluate the demographics and clinical characteristics of patients with pulmonary embolism treated in medical intensive care unit (ICU) at the University Hospital during a six-year period, and to assess the impact of several risk factors on patients’ survival. The study included 165 patients, mean age 69.3 ± 13.7 years, predominantly female (70.3%). Dominant symptom was dyspnea (97.0%), the most common sign tachypnea (69.6%). Pulmonary embolism was confirmed by high-probability ventilation/perfusion lung scan or multidetector computed tomography in 71.5% and was regarded as massive in 63 (38.2%), submassive in 23 (13.9%) and non massive in 79 patients (47.9%). Mean hospital stay was 5.7 ± 4.4 days for ICU, and 14.8 ± 9.1 days, overall. The ICU mortality was 26.7% and in-hospital mortality 30.9%. No statistical difference in mortality between male and female patients was observed (30.6% and 31.0%, respectively; p=0.965), but prolonged immobilization (p=0.002), recent operation (p=0.034) or malignancy (p=0.009) were shown to influence the outcome. Although a number of risk factors for developing pulmonary embolism have been identified and heparin prophylaxis along with early mobilization proposed to reduce the incidence, pulmonary embolism remains an important clinical problem with high mortality rate. The diagnostics should not wait and the therapy should start as soon as possible